2022
DOI: 10.1371/journal.pcbi.1009859
|View full text |Cite
|
Sign up to set email alerts
|

STENCIL: A web templating engine for visualizing and sharing life science datasets

Abstract: The ability to aggregate experimental data analysis and results into a concise and interpretable format is a key step in evaluating the success of an experiment. This critical step determines baselines for reproducibility and is a key requirement for data dissemination. However, in practice it can be difficult to consolidate data analyses that encapsulates the broad range of datatypes available in the life sciences. We present STENCIL, a web templating engine designed to organize, visualize, and enable the sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Many studies have been reported on e cient and accurate means of identifying DEGs [4][5][6]. This includes statistical methods [7][8][9], data normalization methods [10][11][12][13][14], R packages [15][16][17][18], and graphical user interfaces [19][20][21][22]. Conventional differential expression (DE) analysis such as edgeR [15] and DESeq2 [16] typically consists of two steps (data normalization X and DEG identi cation Y), and each R package has its own methods for the X-Y pipeline [23].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on e cient and accurate means of identifying DEGs [4][5][6]. This includes statistical methods [7][8][9], data normalization methods [10][11][12][13][14], R packages [15][16][17][18], and graphical user interfaces [19][20][21][22]. Conventional differential expression (DE) analysis such as edgeR [15] and DESeq2 [16] typically consists of two steps (data normalization X and DEG identi cation Y), and each R package has its own methods for the X-Y pipeline [23].…”
Section: Introductionmentioning
confidence: 99%